Potencial uporabe mezenhimskih matičnih celic maščobnega izvora za zdravljenje atopijskega dermatitisa - Bizjak, Ela (Placebo, 2025)
Atopic dermatitis (AD) is a complex, chronic infl ammatory skin disease characterized by itching, infl ammation, and dryness of the skin. The causes of the disease are multifactorial and not fully understood. They involve dysfunction of the immune system, damage to the skin barrier, genetic predispositions, and changes in the skin microbiome. Various types of T cells (Th1, Th2, Th17, Th22), mast cells, and eosinophils participate in the immune response, releasing infl ammatory cytokines that cause acute and chronic infl ammation. Genetic mutations, particularly in the gene for fi laggrin, further weaken the skin barrier. Microbiome alterations, especially colonization of the skin by Staphylococcus aureus, further worsen the condition. Traditional treatment is based on corticosteroids and immunomodulators, but these have numerous side eff ects and are prone to resistance development. Recent studies have identifi ed adipose-derived mesenchymal stem cells (AD-MSCs) as a promising therapy, as their low immunogenicity and strong immunomodulatory and regenerative properties help suppress infl ammation and repair damaged skin. Moreover, their isolation is less invasive compared to other types of mesenchymal cells.
Keywords: adipose derived mesenchymal stem cells; atopic dermatitis; atopijski dermatitis; celice T-pomagalke tipa 2; Dermatitis; filaggrin; filagrin; kožna bariera; Mezenhimske matične celice; mezenhimske matične celice maščobnega izvora; microbiome; mikrobiom; skin barrier; T helper 2 cells